2018
DOI: 10.1007/s10802-018-0445-3
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Impulsivity: A Meta-Analysis and Recommendations for Future Study

Abstract: Both childhood maltreatment and impulsivity have been implicated in a broad array of negative public health outcomes and have been much studied in relation to each other. Characterizing this relationship, and the processes underlying it, are important for informing intervention efforts targeting this association and its psychopathological sequelae. The current review presented a systematic meta-analysis of the empirical literature on childhood maltreatment and impulsivity. In all, 55 eligible studies were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 153 publications
(132 reference statements)
6
55
0
2
Order By: Relevance
“…A meta-analysis of 217 publications has reported a global prevalence of 12% on the basis of 331 independent samples comprising about 10 million individuals. 1 Studies have reported associations between childhood sexual abuse and many psychosocial and health-related outcomes, including psychosocial problems, 2,3 self-harm, 4 psychiatric disorders, [5][6][7] and physical health diagnoses such as HIV 8 and obesity. 9 These reports have raised important questions about the extent of association between childhood sexual abuse and long-term outcomes in adulthood, the relative effects of childhood sexual abuse on different outcomes, and the quality of the current research base.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 217 publications has reported a global prevalence of 12% on the basis of 331 independent samples comprising about 10 million individuals. 1 Studies have reported associations between childhood sexual abuse and many psychosocial and health-related outcomes, including psychosocial problems, 2,3 self-harm, 4 psychiatric disorders, [5][6][7] and physical health diagnoses such as HIV 8 and obesity. 9 These reports have raised important questions about the extent of association between childhood sexual abuse and long-term outcomes in adulthood, the relative effects of childhood sexual abuse on different outcomes, and the quality of the current research base.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this possibility is increased by the hereditary nature of impulsivity in children with impulsive parents. In other words, parents who have been exposed to wrong parenting practices and maltreatment are more likely to have impulsive children (8). Generally, in exposure to childhood maltreatment and abuse, the developing part of the brain is the most affected part, that is, the hippocampus from birth until the age of two years, the amygdala in early childhood, and the prefrontal cortex during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in exposure to childhood maltreatment and abuse, the developing part of the brain is the most affected part, that is, the hippocampus from birth until the age of two years, the amygdala in early childhood, and the prefrontal cortex during adolescence. It is argued that poor development of the frontal cortex during adolescence, compared to other periods of development, is strongly correlated with the experience of abuse and impulsivity (8,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impulsivity, the focus of the next paper (Hallowell et al, 2019), is a multifactorial construct implicated in substance use disorders (Lee, Hoppenbrouwers, & Franken, 2019) and child maltreatment (Liu, 2019). In this study, Hallowell and colleagues (2019) investigated the impact of child maltreatment on impulsivity via functional magnetic resonance imaging (fMRI) during a verbal working memory task in a sample of emerging adult females (ages 18–25 years).…”
mentioning
confidence: 99%